Supporting implementation of interventions to address ethnicity-related health inequities: frameworks, facilitators and barriers – a scoping review protocol - Sue Crengle; Peter Carswell; Rachel Brown; Karen Bartholomew; Michelle Lambert; Patricia Priest; Adam Fusheini; Papillon Gustafson; Yasmin Abdul Aziz; Mihi Ratima (BMJ Open)
Introduction Health inequities are differences in health between groups of people that are avoidable, unfair and unjust. Achieving equitable health outcomes requires approaches that recognise and account for the differences in levels of advantage between groups. Implementation science, which studies how to translate evidence-based interventions into routine practice, is increasingly recognised as an approach to address health inequities by identifying factors and processes that enable equitable implementation of interventions. This article describes the protocol for a scoping review of the literature relating to the equitable implementation of interventions, focusing on ethnicity-related health inequities. The scoping review aims to identify equity-focused implementation science theories, models and frameworks (TMFs) and to synthesise and analyse the evidence relating to the factors that aid or inhibit equitable implementation of health interventions.Methods and analysis The scoping review is guided by the methodology developed by Arksey and O’Malley and enhanced by Levac and colleagues. Relevant literature will be identified by searching electronic databases, grey literature, hand-searching key journals and searching the reference lists and citations of studies that meet the inclusion criteria. We will focus on literature published from 2011 to the present. Titles, abstracts and full-text articles will be screened independently by two researchers; any disagreements will be resolved through discussion with another researcher. Extracted data will be summarised and analysed to address the scoping review aims.Ethics and dissemination The scoping review will map the available literature on equity-focused implementation science TMFs and the facilitators and barriers to equitable implementation of interventions. Ethical approval is not required. Dissemination of the results of the review will include publications in peer-review journals and conference and stakeholder presentations. Findings from the review will support those implementing interventions to ensure that the implementation pathway and processes are equitable, thereby improving health outcomes and reducing existing inequities.